Validity of the two-parameter model in estimating the anaerobic work capacity - Dekerle, J.; Brickley, G.; Hammond, A. J. P.; Pringle, J. S. M.; Carter, H. (European Journal of Applied Physiology, 2005)
The curvature of the power-time (P-t) relationship (W'has been suggested to be constant when exercising above critical power (CP) and to represent the anaerobic work capacity (AWC). The aim of this study was to compare W' to (1) the total amount of work performed above CP (W90s') and (2) the AWC, both determined from a 90s all-out fixed cadence test. Fourteen participants (age 30.5±6.5 years; body mass 67.8±10.3 kg), following an incremental VO2max ramp protocol, performed three constant load exhaustion tests set at 103±3, 97±3 and 90±2% P-VO2max to calculate W from the P-t relationship. Two 90s all-out efforts were also undertaken to determine W90s' (power output- time integral above CP) and AWC (power output- time integral above the power output expected from the measured VO2). W' (13.6±1.3 kJ) and W90s' (13.9±1.1 kJ; P=0.96) were not significantly different but were lower than AWC (15.9±1.2 kJ) by 24% (P=0.03) and 17%, respectively (P=0.04). All these variables were correlated (P<0.001) but great extents of disagreement were reported (0.2±6.4 kJ between W' and W90s', 2.3±7.2 kJ between W' and AWC, and 2.1±4.3 kJ between W90s' and AWC). The underestimation of AWC from both W' and W90s' can be xplained by the aerobic inertia not taking into consideration when determining the two latter variables. The low extents of agreement between W', W90s' and AWC mean the terms should not be used interchangeably.